THE USAGE OF PAUSE PROCEDURE METHOD IN THE LECTURES AND POSITIVE AND NEGATIVE SIDES OF ITS IMPLEMENTATION - Turdiyeva Zahro Mirsoliyevna, (TADQIQOTLAR, 2025)
The Pause Procedure teaching strategy has emerged as an effective method to enhance  learning  outcomes  in  lecture-based  instruction.  This  strategy  involves introducing  short,  structured  pauses  during  lectures  to  provide  students  with opportunities  to  reflect,  review,  and  engage  actively  with  the  material.  Research demonstrates  its  effectiveness  in  improving  comprehension,  retention,  and  overall engagement. Studies by Ruhl, Hughes, and Schloss (1987), Bonwell and Eison (1991), and others highlight the strategy's ability to break the monotony of traditional lectures, foster critical thinking, and create dynamic learning environments. This article explores the  theoretical  underpinnings,  practical  applications,  and  benefits  of  the  Pause Procedure in lectures. Specific activities for implementing the strategy, such as peer discussions, note reviews, and quick assessments, are discussed in detail, alongside challenges and solutions for diverse educational contexts. The article concludes with evidence-based recommendations for integrating the Pause Procedure to maximize its potential in higher education.